Strategi Pertamina sebagai Global Norms Translator Indonesia dalam Mengimplementasikan COP Periode 2015-2024 - Manopo, Zeffanya Tessalonika; Paskarina Alfalahsea (Department of International Relations, Brawijaya University, 2026)
This article analyzes Indonesia’s strategy in translating global climate norms originating from the Conference of the Parties (COP) under the UNFCCC framework into national energy policy and corporate governance through the case of PT Pertamina (Persero). The objective is to explain how Pertamina acts as a global norms translator that mediates between international decarbonization expectations and national energy sovereignty. The research employs a qualitative case study using document analysis and process tracing to examine policy integration and institutional adaptation. Data were obtained from government policy documents such as the Kebijakan Energi Nasional (KEN), Rencana Umum Energi Nasional (RUEN), and Long-Term Strategy for Low Carbon and Climate Resilience (LTS-LCCR), as well as Pertamina’s sustainability reports and financial frameworks. Guided by the theoretical perspectives of constructivism, norm localization (Acharya, 2004), and norm contestation (Wiener, 2016), the study identifies a multi-level process of norm diffusion consisting of emergence, translation, contestation, internalization, and reproduction. The findings reveal that Pertamina institutionalizes COP norms through the Environmental, Social, and Governance (ESG) Framework and the Sustainable Finance Framework (SFF), integrating sustainable finance and low-carbon innovation into corporate governance. Initiatives such as geothermal development, carbon capture, and sustainable fuel projects illustrate the localized adaptation of global norms to Indonesia’s energy transition agenda. The study concludes that Pertamina’s evolution from norm recipient to norm entrepreneur reflects Indonesia’s growing normative agency in shaping an inclusive and equitable global energy governance architecture.